Availability of Family-Friendly Work Practices and Implicit Wage Costs: New Evidence from Canada - Ali Fakih (Institute for the Study of Labor (IZA), 2014)
Using Canadian linked employer-employee data covering the period 1999-2005, I examine the determinants of the availability of family-friendly "care" practices and the impact of such practices on wages. The results show that the provision of family-friendly practices is not mainly derived from socio-demographic characteristics of workers but rather from job- and firm-related factors. The findings also reveal that there is a trade-off between the provision of family-friendly practices and earnings indicating the existence of an implicit market in which workers face reductions in their wages. This result supports the hypothesis that family-friendly benefits are to some extent conceived as a gift or a signal that employers care about employees' family responsibilities and, in return, employees are willing to buy these practices and thus accept a wage offset.
Keywords: J13; J32; J70; 330; family-friendly "care" practices; linked employer-employee data; simultaneous probit model; wage equation